Cellular Automata Application for Simulation of UraniumCrystallization Process; Chemical Engineering Transactions; Vol. 52 - Ochoa Bique A. O. Anton Orlandovich; Serikov D. A. Dmitry Aleksandrovich; Goryunov A. G. Aleksey Germanovich; Manenti F. Flavio (2016, 2016)
Title screen